Bimbingan dan Konseling Islam dengan Terapi Rasional Emotif dalam Mengatasi Siblingrivalry dalam Keluarga di Desa Grabagan Kecamatan Tulangan Kabupaten Sidoarjo (Jurnal Bimbingan dan Konseling Islam, 2017)
In this thesis there are two problems studied, namely (1) How is the process of Islamic guidance and counseling with emotive rational therapy in overcoming the sibling rivalry in the family in Sidoarjo? (2) How is the end result of the process of guidance and counseling with emotive rational therapy in the categorical in the family in Sidoarjo? In answering the problem, this research uses a qualitative method with a comparative descriptive approach of comparing theoretical data with the data in the field. The counsellor used emotive Rational therapy in carrying out his treatment process. Questions and answers while thinking irrational thoughts towards rational, become one of the ways in the process of therapy, so that the thought of Eklidan Ergi is always directed to think rational, including both his parents and the second child who Named Ikma. Through that way, they can slowly eliminate the irrational mind of mind, and be transformed into a rational mind of mind. While the final result of the study shows that the family has undergone significant changes, the change is heading in a better direction. In fact, they have been sorry for the apology and have re-gathered together in a harmonious family, so they already feel safe and comfortable in the family.